A hybrid finite-volume finite-difference rotational Boussinesq-type model of surf-zone hydrodynamics - Tatlock, Benjamin (2015)
An investigation into the numerical and physical behaviour of a hybrid finite-volume finite-difference Boussinesq-type model, using a rotational surface roller approach in the surf-zone is presented. The relevant theory for the required development of a numerical model implementing this technique is outlined. The proposed method looks to achieve a more physically realistic description of the hydrodynamics by considering the rotational nature of the highly turbulent flow found during wave breaking. This involves a semi-analytical solution to the vorticity transport equation and provides a mechanism by which energy is dissipated. Resolving vorticity within the flow also allows vertical profiles of the horizontal velocity to be constructed, offering valuable detail that is otherwise unavailable when using equivalent irrotational Boussinesq-type models. By obtaining additional information about the structure of the flow, other quantities can be determined, such as the undertow, which has a key role in morphodynamic processes occurring in this region. These benefits are combined with a finite-volume finite-difference scheme, which yields improvements in stability and possesses inherent shock-capturing capabilities.